PENERAPAN DISIPLIN KELAS UNTUK MENINGKATKAN HASIL BELAJAR SISWA SEKOLAH DASAR - Fatimatul Azzahra, Dhela; Sabita Rahmawati, Dhiya; May Astiningsih, Dwiana; Evelin Tampubolon, Exsa; Salsabila, Felisha; Iskandar, Sofyan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to: (1) identify the definition of classroom discipline; (2) examine the benefits of disciplined classroom behavior; (3) explain the importance of classroom discipline for elementary school students; (4) determine the impact of disciplined behavior on elementary school students; and (5) analyze the influence of classroom discipline on students’ learning outcomes. The research employs a qualitative approach using a literature review method. As a methodological paradigm, literature research fundamentally utilizes a wide range of literary sources as the primary data corpus, including dictionaries, documents, scientific journals, and other relevant publications. The results of the study indicate that classroom discipline contributes to the creation of an orderly, safe, and conducive learning environment, where effective interactions between teachers and students can take place.